The Role of Innovation on Performance in Banking Sector: A Bibliometric Analysis - Tina Sekar Ayuning Tyas; Syarifa Hanoum; Santy Dwi Cempaka; Uliyatun Nikmah (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Purpose – The banking industry has undergone significant transformation in recent decades, driven by rapid technological advances and regulatory changes. This study aims to explore the development of research related to the impact of innovation on banking performance. Methodology – This study analyses a total of 211 full-text articles from Scopus database using VOSViewer software and content analysis approach. Findings – This study found a significant increase in publications related to banking innovation since 2013. The journals